2016
DOI: 10.1016/j.bjm.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Process optimization for production and purification of a thermostable, organic solvent tolerant lipase from Acinetobacter sp. AU07

Abstract: The purpose of this study was to isolate, purify and optimize the production conditions of an organic solvent tolerant and thermostable lipase from Acinetobacter sp. AU07 isolated from distillery waste. The lipase production was optimized by response surface methodology, and a maximum production of 14.5 U/mL was observed at 30 °C and pH 7, using a 0.5% (v/v) inoculum, 2% (v/v) castor oil (inducer), and agitation 150 rpm. The optimized conditions from the shake flask experiments were validated in a 3 L lab scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 38 publications
1
35
2
3
Order By: Relevance
“…In agreement with the current results, Lilie et al, (2005) reported that the activity of the thermo alkalophilic lipase produced by B. thermoleovorans CCR11 was inhibited in the presence of Hg 2+ , while Ca 2+ enhanced it. However, these results represent a shift from the reports of Sharma et al, (2001) ;Gururaj, (2014), who observed that the activity of lipase produced by Bacillus sp. RSJ-1and Acinetobacter sp.…”
Section: Effects Of Various Metal Ions On Lipase Activitycontrasting
confidence: 83%
“…In agreement with the current results, Lilie et al, (2005) reported that the activity of the thermo alkalophilic lipase produced by B. thermoleovorans CCR11 was inhibited in the presence of Hg 2+ , while Ca 2+ enhanced it. However, these results represent a shift from the reports of Sharma et al, (2001) ;Gururaj, (2014), who observed that the activity of lipase produced by Bacillus sp. RSJ-1and Acinetobacter sp.…”
Section: Effects Of Various Metal Ions On Lipase Activitycontrasting
confidence: 83%
“…RSJ-1, B. thermoleovorans ID-1, Bacillus LBN2, Cohnella sp. A01, B. licheniformis Ht7, and B. sonorensis 4R which were 67.0 kDa, 60.0 kDa, 59.0 kDa, 57.0 kDa, 50.0 kDa, 45.0 kDa, 40.0 kDa, 39.0 kDa, 37 kDa, 34.0 kDa, 33.0 kDa, 29.5 kDa, 22.0 kDa, and 21.87 kDa, respectively, as determined using sodium dodecyl sulfate- (SDS-) polyacrylamide gel electrophoresis (PAGE) [ 4 , 9 , 11 , 18 , 23 , 26 , 27 , 29 – 33 , 54 , 69 71 ].…”
Section: Characteristics Of Ta Lipasesmentioning
confidence: 99%
“…Similarly, TA lipase from Acinetobacter sp. with sequence similar to GDSL family of lipases had an optimum temperature and pH of 50°C and 8.0, respectively [ 27 ]. The TA lipase from T. coremiiforme V3 which was cloned into plasmid pPICZ α A and overexpressed in P. pastoris X33 showed temperature tolerance at 60°C and retained about 45% of lipase activity at 70°C after 60 min [ 72 ].…”
Section: Characteristics Of Ta Lipasesmentioning
confidence: 99%
“…Bacterial lipases are mostly extracellular and their production is influenced by fermentation conditions such as temperature, pH, inoculum size, agitation, carbon sources, inducer sources and concentrations [26][27][28]. The search for optimal conditions of the above-mentioned parameters for lipase production in fermentation processes is imperative in order to obtain high yields of the enzyme at lower costs.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely used to identify effective factors, study interactions, select optimum conditions and quantify the relationships between one or more measured responses and the vital input factors in a limited number of experiments [11,30]. Furthermore, RSM has been successfully applied to evaluate and optimize the effect of process parameters in the production of lipase [28,31,32]. A central composite design (CCD) is the most commonly used response surface design when the experimental design is defined by the upper and lower limits of each parameter [16,33].…”
Section: Introductionmentioning
confidence: 99%